Transrectal US and endorectal MR imaging in partial and complete obstruction of the seminal duct system. A comparative study - Engin, G; Kadioglu, A; Orhan, I; Akdöl, S; Rozanes, I (Sage Publications Ltd, 2000)
Purpose: To evaluate transrectal ultrasonography (US) and MR imaging findings of infertile patients with suspected complete or partial obstruction of the seminal duct system. Material and Methods. Two hundred and eighteen infertile patients with low ejaculate volume were evaluated by transrectal US. Endorectal MR imaging was performed on 62/218 patients. Prostatic cysts, ejaculatory duct (ED) dilatation (>2 mm in width), ED calculi or calcifications, seminal vesicle (SV) dilatation (a.p. diameter >15 mm), SV hypo/agenesis (a.p. diameter <7 mm), SV cysts (>5 mm), vasal agenesis and chronic prostatitis (coarse calcifications, heterogeneity in prostate) were considered significant findings for obstruction of the seminal duct system. Results. Pathologic findings were detected in 75% and 61% of patients with azoospermia on transrectal US and MR imaging, respectively. Transrectal US and MR imaging did not reveal any pathologies in 64.7% and 59.1% of patients with nonazoospermia, respectively. The incidences of hypoplastic/atrophic SV (12/48 vs. 5/170), SV agenesis (6/48 vs. 1/170), vasal agenesis (5/48 vs. 1/170) were significantly higher in the azoospermic subgroup (p<0.002). Conclusion: US is a good method for initial evaluation of these patients especially in complete obstruction. Endorectal MR imaging should be reserved for selected patients in whom results of transrectal US are not conclusive.
Keywords: prostate, ejaculatory duct; seminal vesicle, cysts; ultrasonography, MR imaging